Influence of anxiety on university students’ academic involution behavior during COVID-19 pandemic: Mediating effect of cognitive closure needs - Yan, Dongdong; Zhang, Huanzhe; Guo, Shili; Zeng, Wen (Frontiers in Psychology, 2022)
The COVID-19 pandemic has had a significant negative effect on university students’ mental health worldwide. The pandemic has resulted in individuals experiencing increased levels of anxiety and stress as well as intensified concerns about the future due to a rise in uncertainty. To eliminate the anxiety and stress caused by uncertainty, individuals who have high cognitive closure needs are strongly motivated to achieve certainty and seek answers, even if the decisions they make in the process are inappropriate or even irrational. This study attempts to analyze the influence of anxiety and stress on university students’ academic involution behavior during the COVID-19 pandemic through the mediating effect of the need for cognitive closure. Analyzing the survey data collected from 402 university students from 3 different universities through the mediating effect model and path analysis with latent variable (PA-LV), our results indicate that: (1) the COVID-19 pandemic has significantly increased the levels of anxiety and stress experienced by university students. The path coefficient of the perceived risk of contracting COVID-19 to perceived emotions (including anxiety and stress) was 0.352 (p<0.01), (2) anxiety and stress significantly and positively affect academic involution behavior. For each unit of increase in the scores of anxiety and stress, the scores of academic involution behavior increased by 0.408 (p<0.01) and 0.398 (p<0.01) units respectively, and (3) the need for cognitive closure had a complete and partial mediating effect on the relationship between the perceived risk of contracting COVID-19 and academic involution behavior, as well as anxiety and academic involution behavior, respectively. The results of PA-LV showed that the mediating effect values were 0.106 and 0.044, respectively. The impact of the COVID-19 pandemic has not yet come to an end and so clarifying the relationship between anxiety and academic involution behavior will assist university students to optimize the relationship in their own subjective situations, to establish good learning habits and reduce psychological distress.